Antiviral CD8 T cells induce Zika-virus-associated paralysis in mice. (February 2018) - Jurado, Kellie; Yockey, Laura; Wong, Patrick; Lee, Sarah; Huttner, Anita; Iwasaki, Akiko
Abstract Zika virus (ZIKV) is an emerging, mosquito-borne RNA virus. The rapid spread of ZIKV within the Americas has unveiled microcephaly1 and Guillain–Barré syndrome2, 3 as ZIKV-associated neurological complications. Recent reports have also indicated other neurological manifestations to be associated with ZIKV, including myelitis4, meningoencephalitis5 and fatal encephalitis6 . Here, we investigate the neuropathogenesis of ZIKV infection in type I interferon receptor IFNAR knockout (Ifnar1 −/− ) mice, an infection model that exhibits high viral burden within the central nervous system. We show that systemic spread of ZIKV from the site of infection to the brain requiresIfnar1 deficiency in the haematopoietic compartment. However, spread of ZIKV within the central nervous system is supported byIfnar1 -deficient non-haematopoietic cells. Within this context, ZIKV infection of astrocytes results in breakdown of the blood–brain barrier and a large influx of CD8+ effector T cells. We also find that antiviral activity of CD8+ T cells within the brain markedly limits ZIKV infection of neurons, but, as a consequence, instigates ZIKV-associated paralysis. Taken together, our study uncovers mechanisms underlying ZIKV neuropathogenesis within a susceptible mouse model and suggests blood–brain barrier breakdown and T-cell-mediated neuropathology as potential underpinnings of ZIKV-associated neurological complications in humans. Zika virus infection of astrocytes inIfnar –/– mice results in breakdown of the blood–brain barrier and CD8+ effector T-cell infiltration, which limits neuron infection but leads to Zika-virus-associated paralysis.